Project-Based Authentic Assessment to Enhance Student Learning Activities at SMPN 12 Malang - Nurfadhila, Afifah Asri; Rahutami; Suwanik Hariati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the implementation of project-based authentic assessment to improve students' learning activity in procedural text instruction at SMP Negeri 12 Malang. The study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, conducted in two cycles involving 32 students of Class IX F. Data were collected through classroom observations, project assessments, documentation, and pre-tests and post-tests, and were analyzed using descriptive quantitative and qualitative techniques with data triangulation. The findings revealed that the average level of students' learning activity increased from 47% in the pre-cycle to 73% in Cycle I and 88% in Cycle II. Students' mean achievement score also improved from 46.4 to 67.9, while the percentage of learning mastery increased from 14.3% to 68%. These findings indicate that the implementation of authentic assessment through a profession-based procedural text project effectively enhanced students' learning activity and conceptual understanding while fostering more contextual and meaningful learning in accordance with the principles of the Merdeka Curriculum.